An ex vivo culture model for orthodontically induced root resorption - Wan Hassan, Wan Nurazreena; Stephenson, Pamela A.; Waddington, Rachel J.; Sloan, Alastair J. (Elsevier, 2012)
OBJECTIVES: Root resorption is a ubiquitous although undesirable sequela to orthodontic treatment. Current methods to investigate the pathophysiology have certain limitations. In pursuit to understand and develop treatment modalities for orthodontically induced root resorption, the ability to manipulate cells within their natural extracellular matrix in a three dimensional organotypic model is invaluable. The study aimed to develop a laboratory-based organotypic model to investigate the effect of orthodontic forces on the periodontium. METHODS: Mandibular slices of male Wistar rats were maintained in Trowel-typed cultures at 37°C in 5% carbon dioxide in air for 7days with test specimens subjected to compressive forces at 50g and 100g by stainless steel springs. Tissue architecture and cell viability were maintained under culture conditions. RESULTS: Osteoclast numbers increased significantly in both test groups whilst odontoclasts increased in the 50g group. Immunohistochemistry demonstrated increased dentine sialoprotein expression in both test groups, suggesting changes in mineralization-related activity due to mechanical strain. CONCLUSION: The study showed initial cellular and molecular changes of key markers that relate to root resorption in response to mechanical loading. CLINICAL SIGNIFICANCE: Severe root resorption may occur when forces applied are heavy or transmitted over an extended period and could lead to mobility and tooth loss. This ex vivo model can be used to investigate cellular and molecular processes during orthodontic tooth movement which may advance the clinical management of root resorption.